Global Value Chain Analysis on PT Batik Keris Surakarta - Anisa Risanti Suhita; Ferdian Ahya Al Putra; Gregorius Bunga Nanda Jiwa (Journal of World Trade Studies, 2021)
Batik is an Indonesian cultural heritage that has been recognized by The United Nations Educational, Scientific and Cultural Organization (UNESCO). In addition to cultural heritage, many Indonesian people live through Batik crafts. Batik Keris is one of the Lead Firms in the Batik industries in Surakarta, even in Indonesia, where it plays an important role in the Batik industry and also in preserving Batik itself. This study examines the global value chain of PT. Batik Keris and their role as Lead Firm in the Batik industry and their relationship with the Surakarta City Government program. This study uses a qualitative descriptive method by applying the Global Value Chain Concept introduced by Gerry Gereffi (2016). Meanwhile, the data was obtained through interviews with related sources and literature studies. The results show that Batik Keris has implemented an upgrade strategy ranging from design, use of technology, to carry out various activities such as fashion shows and Batik Carnival. Keywords: Batik Industry, Batik Keris, Global Value Chain, Local Economic Development